Expressões idiomáticas do português sob a perspectiva da Gramática Discursivo-Funcional - Silva, Diogo Oliveira da (Universidade Federal de São Carlos, 2025)
The general aim of this thesis is to investigate, in light of the Functional Discourse Grammar (FDG) (Hengeveld; Mackenzie, 2008) and studies by Keizer (2016, 2018), the semantic-cognitive status of idiomatic expressions (IEs) in Portuguese, using, as guiding principles, motivation, for a cognitive analysis, and compositionality, for a morphosyntactic analysis, in order to define degrees of transparency and opacity of IEs, with the purpose of proposing a typology of IEs for Portuguese. To achieve this aim, based on Keizer (2016, 2018), a set of fourteen morphosyntactic variation criteria is applied, namely: lexical substitution, adjectival modification, quantification, number, definiteness, passivization, nominalization, anaphoric reference, cataphoric reference, insertion of adverbs, insertion of pronouns, inversion of the preferred order, elision of a fixed term and possibility of conversion to imperative mode. From an initial compilation of IEs already included in dictionaries (Riva, 2009; Silva, 1997; Almeida, 2022), data collection took place, which took into account the Reference Corpus of Contemporary Portuguese (2016), written records from the web and constructed data. In view of this universe of research, the specific aims sought are: (i) to verify how the speaker's extra cognitive effort process functions, involved in the reanalysis of IEs; (ii) to check the IEs according to the alignment among the Interpersonal, Representational and Morphosyntactic levels of the FDG; and (iii) to determine how the violation of the one-to-one relationship between form and meaning of the constituent elements of the IEs occurs (Leufkens, 2015). After applying the criteria, performing the cognitive and morphosyntactic analysis of the occurrences, verifying their degree of transparency and the alignment among the levels of the model, it was possible to identify, in Portuguese, in addition to the four types of IEs found in English by Keizer (2016), a new typology, comprising the following set: (i) unmotivated and non-decomposable; (ii) motivated and non-decomposable; (iii) motivated and decomposable; (iv) AD-HOC expressions, with specific use; and the last type, (v) partially motivated by conceptual metaphors and decomposable ones. In addition to identifying this fifth type of IE in Portuguese, this research also adds to Keizer's (2016) discussion of cases of AD-HOC IEs, involving discontinuity and context dependence, and attests to the applicability of the set of primitives CombPIF – Combination of partially instantiated frames (Keizer, 2016), now with results in IEs of Lusophone varieties of Portuguese, which can contribute to expanding research horizons on the metaphorical interpretation of IEs in light of the FDG.
Portuguese idiomatic expressions from the perspective of Functional Discourse Grammar
Expresiones idiomáticas del portugués desde la perspectiva de la Gramática Discursivo-Funcional
Keywords: Expressões idiomáticas; Motivação; Composicionalidade; Gramática Discursivo-Funcional; Idioms; Motivation; Compositionality; Functional Discourse Grammar; LINGUISTICA, LETRAS E ARTES::LETRAS::LINGUA PORTUGUESA; LINGUISTICA, LETRAS E ARTES::LETRAS; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade